John W.A. Sanford, The Code of the City of Montgomery, Prepared in Pursuance of an Order of the City Council of Montgomery 50, § 129 (1861) - (:unkn) unknown (My University, 1861)
Prohibited the discharge of any gun, pistol, or any kind of fire-arms within city limits. Violators fined five dollars.
Keywords: DISCHARGE